Metabolic reprogramming and immune regulation in acute myeloid leukemia - Hao, Xiaogang; Fan, Chenyang; Yan, Lixiang; Jianati, Reaila; Guo, Yifei; Zhou, Xinli; Zhu, Gengda; Zhang, Yucheng; Zheng, Chengyulong; Zhang, Ying; Shi, Zhexin (Frontiers in Immunology, 2025)
The most prevalent kind of acute leukemia in adults is acute myeloid leukemia (AML). While some individuals have had better effectiveness due to advancements in targeted medications, recurrence after remission and inadequate treatment specificity continue to be significant therapeutic problems. By controlling essential metabolic pathways and metabolites, metabolic reprogramming, a crucial strategy for cellular adaptability to energy needs, modifies cellular metabolic rhythms. In addition to being involved in immune cell proliferation, differentiation, and effector function, this pathway is also essential for leukemogenesis and survival signaling in AML. By altering the expression of immune molecules, the release of certain metabolites (such as lactate, ROS, glutamine, etc.) has a significant impact on the immune response to tumors. It is noteworthy that the metabolic interactions between immune cells and AML cells form a distinct pattern of energy competition in the tumor microenvironment. This study examined the new approach of targeting metabolic pathways to improve immunotherapy, systematically clarified the regulatory mechanism of metabolic reprogramming between AML cells and immune cells to counteract tumor immunity, and concentrated on the synergistic effect of current therapies and metabolic interventions. These findings offered a fresh perspective on how to fully realize the potential of metabolic therapy for AML.